Evaluating the Potential of Laser Beam Quality Improvement by Adaptive Optics System. (5th December 2019) - Han, Kai; Cui, Wenda; Yang, Yi; Xi, Fengjie; Li, Xiao; Du, Shaojun
Abstract : AO (adaptive optics) systems have been extensively used to improve the beam quality in high-energy lasers; however, few studies have focused on how much the beam quality could be improved. A novel evaluation criteria and factor is presented in this paper. The factor, defined as power in ring (PIR), is expressed by distinguishing the low- and high-spatial frequency components in the far-field laser intensity distribution. Beams with different PIR values are generated in our model, and then they are compensated by AO systems. Calculation result shows that the PIR factor could evaluate a laser beam's improvement potential by an AO system quantitatively.